Cultural Warping of Childbirth, Revisited - Budin, Wendy C. (Lamaze International, 2007)
In this column, the editor of The Journal of Perinatal Education revisits Doris Haire's classic 1972 article, “The Cultural Warping of Childbirth,” and describes the birth culture of today. The editor also describes the contents of this issue, which offer a broad range of resources, research, and inspiration for childbirth educators in their efforts to promote normal birth.